Consumer Protection Against Illegal Cosmetic Products Produced by Beauty Salons (Study on BBPOM Semarang): Perlindungan Konsumen Terhadap Produk Kosmetik Ilegal yang Diproduksi oleh Salon Kecantikan (Studi pada BBPOM Semarang) - Damaian, Muhammad Iqbal (Faculty of Law, Universitas Negeri Semarang, 2024)
The purpose of this research is to identify and examine legal protection efforts against consumers who use illegal cosmetic products produced by beauty salons, as well as identify and examine the implementation of Law Number 8 Year 1999 on Consumer Protection against beauty salons that produce illegal cosmetics in Semarang City. This research uses qualitative research methods with empirical legal research. The theories used in this research are legal protection theory and supervision theory. The results of this study show that (1) consumer protection efforts against illegal cosmetics have been implemented well and in accordance with the theory of legal protection, and (2) supervision carried out by BPOM and LP2K against illegal cosmetics has been implemented well and in accordance with the provisions of the Consumer Protection Law. Based on the research that has been conducted, it can be concluded that (1) the existence of illegal cosmetic products circulating in the community is caused by the lack of government supervision of illegal cosmetic products, products that are cheap and easily obtained by consumers, and the lack of information for consumers regarding the dangers of illegal cosmetics; (2) the government's efforts to supervise the circulation of illegal cosmetics are in accordance with Law Number 8 of 1999 concerning Consumer Protection, Law Number 17 of 2023 concerning Health, Regulation of the Food and Drug Supervisory Agency Number 23 of 2019 concerning Technical Requirements for Cosmetic Ingredients.